How Ship Managers Perceive the Operational Efficiency of Shipping Companies: A Qualitative Inquiry - Venkadasalam, Saravanan (International Journal of Economics, Management and Accounting, 2022)
In this study, we investigated ship managers' perceptions of shipping companies' operational efficiency. Semi-structured interviews were conducted with five respondents: two from Malaysia and three from Singapore. Further, we constructed four new themes from the interviews, consisting of fifteen categories and eighty-eight new subcategories. In general, this paper proposed two new conceptual frameworks and an improvised physical-efficiency model. This paper is the first to analyze the shipping efficiency qualitatively in this region to the best of our knowledge.